Hypertension and Socioeconomic Status in South Central Uganda: A Population-Based Cohort Study - Mustapha, Aishat; Ssekasanvu, Joseph; Chen, Ivy; Kathryn Grabowski, Mary; Ssekubugu, Robert; Kigozi, Godfrey; Reynolds, Steven J.; Gray, Ronald H.; Wawer, Maria J.; Kagaayi, Joseph; Chang, Larry W.; Post, Wendy S. (Global Heart, 2022)
Limited studies exploring the impact of socioeconomic status (SES) on hypertension in Africa suggest a positive association between higher SES and hypertension. The economic development in sub-Saharan African countries has led to changes in SES and associated changes in lifestyle, diet, and physical activity, which may affect the relationship between hypertension and SES differently compared with higher income countries. This cross-sectional study from a large populationbased cohort, the Rakai Community Cohort Study (RCCS), examines SES, hypertension prevalence, and associated risk factors in the rural Rakai Region in south-central Uganda. Methods: Adults aged 30–49 years residing in 41 RCCS fishing, trading, and agrarian communities, were surveyed with biometric data obtained between 2016 and 2018. The primary outcome was hypertension (systolic blood pressure (BP) ≥ 130 mmHg or diastolic BP ≥ 80 mmHg). Modified Poisson regression assessed the adjusted prevalence ratios (PR) of hypertension associated with SES; body mass index (BMI) was explored as a potential mediator. Results: Among 9,654 adults, 20.8% had hypertension (males 21.2%; females 20.4 %). Participants with hypertension were older (39.0 ± 6.0 vs. 37.8 ± 5.0; p < 0.001). Higher SES was associated with overweight or obese BMI categories (p < 0.001). In the multivariable model, hypertension was associated with the highest SES category (aPR 1.23; confidence interval 1.09–1.38; p = 0.001), older age, male sex, alcohol use, and living in fishing communities and inversely associated with smoking and positive HIV serostatus. When BMI was included in the model, there was no association between SES and hypertension (aPR 1.02; CI 0.90–1.15, p = 0.76). Conclusion: Hypertension is common in rural Uganda among individuals with higher SES and appears to be mediated by BMI. Targeted interventions could focus on lifestyle modification among highest-risk groups to optimize public health impact.
Keywords: Hypertension; Socioeconomic status; Global cardiovascular disease; Cardiovascular disease; Rakai